Analisa Peningkatan Kasus Perceraian di Provinsi DKI Jakarta Studi Kasus Kota Jakarta Timur - Irvan Maulana, Mohammad; Pribadi Garfes, Harry (VISA: Journal of Vision and Ideas, 2026)
This study aims to analyze the increasing divorce cases in DKI Jakarta, with a specific focus on East Jakarta. A mixed-methods approach was employed, combining quantitative analysis of divorce statistics with qualitative analysis through literature review and religious court decision documents. The data were obtained from Statistics Indonesia and the Supreme Court of Indonesia covering the period 2019–2024. The results indicate an upward trend in divorce cases in East Jakarta, with economic factors identified as the primary cause, followed by prolonged marital conflicts, poor spousal communication, and shifts in urban social values. Most cases were filed as divorce lawsuits by wives, reflecting increasing legal awareness and women’s independence. Divorce has significant impacts on family well-being, particularly on children’s psychological and economic conditions. Therefore, comprehensive efforts are required to reduce divorce rates through strengthening premarital education programs, expanding family counseling services, and optimizing mediation processes in religious courts. This study is expected to contribute to policy formulation aimed at enhancing family resilience in urban areas.